State of scientific development of the problems of state anti-corruption policy in Ukraine - Ростовська, Карина Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article is devoted to the state of scientific development of problems of state policy of Ukraine. Analyzed are scientific studies of this subject, questions that have been studied by science. Relying on the scientific achievements of the predecessors, they highlight those aspects that have remained outside the scope of research and require solution. Sacred to the questions of the state of scientific development of problems of public policy of Ukraine. Scientific researches of noted problematiki are analysed, questions which was studied science are outlined. Those aspects which remained out of limits of researches and need decision light up leaning on scientific achievements of predecessors. Determination of the state of scientific development of legal problems of public anticorruption policy is foreseen by the review of literature on an anticorruption subject; systematization of Ukrainian and foreign monographic and other labours in relation to the problems of policy of the state in industry of counteraction a corruption; determination of questions which remained out of eyeshot research workers; formulation of problems tasks of this research. It follows to specify that systematization of scientific researches in a that or other volume is one of methods, which scientists use for the decision of the state of development of problem in industry of counteraction a corruption, establishment of own position and methodology of illumination of theoretical and applied aspects of overcoming of this negative phenomenon. Рroper scientific providing. what foresees organization of scientific researches from the problems of prevention of corruption, bringing them over, to the certain system, development of new suggestions, scientific methods and recommendations, on these questions, their rational introduction in practice, prognostication and scientific analysis of efficiency of application of forms and facilities of fight, with a corruption, and also moral and financial encouragement of authors of these researches, is the necessary condition of increase of efficiency of this activity There are positions of administrativno-pravovoy doctrine of counteraction a corruption in works of these and other research workers. In particular by them certainly role of administrative law in the context of reformation of public power on the modern stage of development of Ukrainian society, providing of rights and freedoms of citizens; influence of corruption is set on public relations in the field of public service; the question of application of measures of administrative compulsion is reflected in discovered and stopping of administrative corruption offences; Conducted study of separate scientific labours from anticorruption problematiki allowed to find out tendencies in directions of scientific search, to set the state of the scientific providing of counteraction a corruption. It is set research, that in domestic dissertations scientific research absents it is devoted the questions of public anticorruption policy. In studied by us afore-mentioned and other scientific labours a public anticorruption policy is examined very narrowly and fragmentary within the limits of other researches, in the context of constituent of public legal policy, as an important factor of reforms and mean of overcoming of corruption and others like that.